0.61=30z

Rewrite the equation as 30z=0.61.

30z=0.61

Divide 0.6 by 1.

30z=0.6

Multiply each term by z and simplify.

Multiply each term in 30z=0.6 by z.

30z⋅z=0.6⋅z

Cancel the common factor of z.

Cancel the common factor.

30z⋅z=0.6⋅z

Rewrite the expression.

30=0.6⋅z

30=0.6z

30=0.6z

Rewrite the equation as 0.6z=30.

0.6z=30

Divide each term by 0.6 and simplify.

Divide each term in 0.6z=30 by 0.6.

0.6z0.6=300.6

Cancel the common factor of 0.6.

z=300.6

Divide 30 by 0.6.

z=50

z=50

z=50

Solve for z 0.6/1=30/z